Rethinking the role of transitions between activities in early childhood settings: An examination of their linguistic characteristics in two preschool classrooms. (December 2021) - Ryan, Ève; Bailey, Alison L; Grace, Yiching H
This study points to ways in which the amount and complexity of teacher talk in two preschool classrooms during transitions between activities differed from instructional activity settings throughout the day. What emerged were language characteristics that suggest not all transitions are created equal. In fact, as shown by qualitative excerpts of teacher–student interactions, some transitions are quite substantive and provide opportunities for rich extended conversations. The findings of this study suggest that, despite the popular perception of transitions as lost instructional time, the informal setting of transitions can be used to reinforce concepts taught in more formal instructional settings such as circle time, as well as opportunities to introduce new concepts and vocabulary following children's lead. Interviews with the teachers of these two classrooms, while revealing their acknowledgment of some challenges (e.g. children's engagement), mostly emphasized the intentional and potentially instructional nature of transitions.